2010
DOI: 10.1149/1.3429009
|View full text |Cite
|
Sign up to set email alerts
|

Overview of SOFC Anode Interactions with Coal Gas Impurities

Abstract: An overview of the results of SOFC anode interactions with phosphorus, arsenic, selenium, sulfur, antimony, and hydrogen chloride as single contaminants or in combinations is discussed. Tests were performed using both anode- and electrolyte-supported cells in synthetic and actual coal gas for periods greater than 1000 hours. Post-test analyses were performed to identify reaction products formed and their distribution, and compared to phases expected from thermochemical modeling. The ultimate purpose of this wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 7 publications
(10 reference statements)
1
3
0
Order By: Relevance
“…In both cells, a visible coating is present on the anode surface after the experiment. As in previous studies, [3][4][5][6][7][8][9][10][11][12][13] this coating yields XRD spectra consistent with nickel phosphide phases.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…In both cells, a visible coating is present on the anode surface after the experiment. As in previous studies, [3][4][5][6][7][8][9][10][11][12][13] this coating yields XRD spectra consistent with nickel phosphide phases.…”
Section: Resultssupporting
confidence: 81%
“…2 Phosphine at 1-10 ppm levels have been shown to be detrimental to the Ni/YSZ anode in a number of studies. [3][4][5][6][7][8][9][10][11][12][13] Depending on conditions, the SOFC may exhibit immediate and continuous degradation of performance, or may operate stably for a hundred hours before exhibiting performance degradation. Post-mortem studies reveal new phases, most often various nickel phosphides, which migrate to the surface of the anode or into large voids in the anode structure.…”
mentioning
confidence: 99%
“…Efforts to lower the degradation rates further (to ∼0.5%/1000 h) while achieving longer (5000 h and beyond) endurance periods are part of the technology development. Initial work is in progress to identify the SOFC tolerance limits to contaminants present in the coal syngas. To achieve an initial target for SOFC module life of 40000 h, a sulfur specification of 30 ppbv has been assumed for this analysis. However, this specification is subject to change as additional insights to the SOFC anode contaminant analysis are gained.…”
Section: Igfc Power Plant System Developmentmentioning
confidence: 99%
“…A PH 3 concentration of 2 ppmv has been measured in the output of one gasifier (2). Numerous studies have shown that 1-20 ppm levels of PH 3 in wet or dry fuels result in loss of power of SOFCs with nickel-based anodes on a time scale of hours to hundreds of hours (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). Post-mortem analyses have identified both nickel phosphide phases and nickel phosphate phases which migrate to voids and to the surface of the anode.…”
Section: Introductionmentioning
confidence: 99%